Complications of diverticular colopathy - Revetria, Ricardo; Asiner, Boris; Maquieira, Gonzalo; Sojo, Enrique (Cirugía del Uruguay, 1981)
In the chapter on Ethiopathogenesis, the histological and functional alterations that they are at the base of this disease. Highlighting the predisposing role played by cellulose-deficient diets.